Examining the Moderating Role of Compensation in the Relationship between Morality and Internal Control to Accounting Fraud - Syahrudin, Muhammad; Susanto, Sani (Jurnal Ekuisci, 2025)
Background.  Micro, Small, and Medium Enterprises (MSMEs) sustainability is threatened by fraud in financial statements, which poses a serious threat, especially in terms of accountability and access to external financing. MSMEs often face limitations in internal control systems, a lack of competent human resources in the financial sector, and weak separation of functions, which opens up loopholes for fraudulent practices. Aim. This study aims to empirically test how compensation moderates the influence of morality and internal control on the tendency of accounting fraud in the UMKM sector in Cimahi City. The study's results are expected to make a theoretical contribution in the development of financial literature and individual morality, as well as a practical contribution in efforts to prevent accounting fraud among MSME actors. Methods. This research uses a quantitative approach using descriptive and verification designs. The population in this study consisted of 25 MSMEs in Cimahi City that had penetrated the global market and were under the auspices of the Department of Trade, Cooperatives, MSMEs, and Industry (Disdagkoperind) of Cimahi City. The sample in this study was the entire population, namely 25 MSMEs, from each MSME, two respondents were taken as a representation of the quality of financial statements, with qualifications as owners and accounting staff. Data analysis in this study was carried out using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) with the help of SmartPLS software. Result. Internal Control on Accounting Fraud through Compensation Suitability has an indirect effect, which means mediation occurs. Conclusion. The results showed that (1) Compensation suitability has an influence on accounting fraud (2) Internal control has a significant effect on accounting fraud with a strong level of influence (3) Internal control has a very significant effect on compensation suitability (4) The indirect effect of Internal Control on Accounting Fraud through Compensation Suitability has an indirect effect which means mediation occurs. (5) Individual morality does not affect internal control or accounting fraud. Implementation. MSMEs should establish transparent, measurable performance-based incentive structures that ensure internal equity and avoid compensation schemes that risk encouraging opportunistic behaviour